An empirical study on logistic service quality, customer satisfaction, and cross-border repurchase intention - Guan Hui; Abdullah Al Mamun; Mohammad Nurul Hassan Reza; Wan Mohd Hirwani Wan Hussain (Heliyon)
Domestic e-retailers acknowledge logistics service quality (LSQ) as a critical success factor in business excellence. However, exponential growth in cross-border e-commerce (CBEC) requires a re-evaluation of the relationship between LSQ and consumers repurchase intention. By integrating the technology acceptance model, this study investigates the impact of LSQ on repurchase intention based on the LSQ (experience)–satisfaction–repurchase intention consequence chain. Data were collected from 466 Chinese consumers who had engaged in online shopping with international vendors. Partial least squares structural equation modeling was employed to examine the effectiveness of the research model. The results reveal that delivery service quality, return logistics services, and cross-border online shopping experiences significantly influence customer satisfaction. Nevertheless, the relationships between delivery information service, delivery stability, price fairness, and customer satisfaction are not supported. Price fairness, cross-border online shopping experience, and customer satisfaction positively affect cross-border repurchase intentions. Additionally, customer satisfaction mediates the relationships between LSQ, price fairness, cross-border online shopping experience, and repurchase intention. The novelty of this study lies in its focus on the cross-border dimension, introducing additional factors, such as price fairness and cross-border online shopping experiences, including other variables that affect LSQ and customer satisfaction, in contrast to domestic e-commerce. This study contributes to the literature by providing new insights into the complex dynamics of LSQ in CBEC and highlighting the nuanced role of customer satisfaction as a mediator in different market contexts. It offers empirical findings and valuable insights into the multiple dimensions of LSQ and customer satisfaction, thus contributing to the body of knowledge.